Analisis Pengaruh Rapat Komite Audit, Audit Internal, dan Whistleblowing System Terhadap Potensi Fraudulent Financial Reporting - Ulvatul Rahmita Putri; Anda Dwiharyadi; Desi Handayani (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This study aims to analyze the influence of audit committee meetings, internal audits, and whistleblowing systems on the potential for fraudulent financial reporting. This research method is a quantitative method. The population in this study were non-bank financial sector companies listed on the Indonesia Stock Exchange in 2021 to 2023. Sampling was selected using the purposive sampling method. Sampling in this study used the perposive sampling technique with the criteria of 42 companies used as samples in this study. The observation period was carried out for 3 years. The results of the study were analyzed using SPSS software version 29.0. The results of this study are that audit committee meetings have a significant negative effect on fraudulent financial reporting, internal audits have no effect on financial reporting, while the whistleblowing system has no effect on fraudulent financial reporting